Functionalized Polymeric Membrane with Enhanced Mechanical and Biological Properties to Control the Degradation of Magnesium Alloy. Issue 8 (14th February 2017) - Wong, Hoi Man; Zhao, Ying; Leung, Frankie K. L.; Xi, Tingfei; Zhang, Zhixiong; Zheng, Yufeng; Wu, Shuilin; Luk, Keith D. K.; Cheung, Kenneth M. C.; Chu, Paul K.; Yeung, Kelvin W. K.
Abstract : To achieve enhanced biological response and controlled degradation of magnesium alloy, a modified biodegradable polymer coating called polycaprolactone (PCL) is fabricated by a thermal approach in which the heat treatment neither alters the chemical composition of the PCL membrane nor the rate of magnesium ion release, pH value, or weight loss, compared with the untreated sample. The changes in the crystallinity, hydrophilicity, and oxygen content of heat‐treated PCL coating not only improve the mechanical adhesion strength between the coating and magnesium substrate but also enhance the biological properties. Moreover, the thermally modified sample can lead to higher spreading and elongation of osteoblasts, due to the enhanced hydrophilicity and CO to CO functional group ratio. In the analyses of microcomputed tomography from one to four weeks postoperation, the total volume of new bone formation on the heat‐treated sample is 10%–35% and 70%–90% higher than that of the untreated and uncoated controls, respectively. Surprisingly, the indentation modulus of the newly formed bone adjacent to the heat‐treated sample is ≈20% higher than that of both controls. These promising results reveal the clinical potential of the modified PCL coating on magnesium alloy in orthopedic applications. Abstract : Schematic illustrating the effects of the change of the ratio between CO and CO before and after the heat treatment as well as release of Mg on osteoblast adhesion and bone formation: (a) Before the heat treatment, cell spreading of osteoblasts diminished and (b) after the heat treatment, cell spreading on the PCL membrane is enhanced.